Investigation on thermal and kinetic dynamics of droplets - Li, Wang (2023)
In recent years, there has been a surge of interest in studying the dynamics of droplets due to their broad range of applications. However, despite their prevalence in nature, accurately predicting and controlling the various behaviours of droplets, such as evaporation and impingement, remains challenging due to the intricate underlying mechanisms involved. This thesis aims to address these challenges by consolidating existing literature and conducting a comprehensive investigation into the thermal and kinetic dynamics of droplets.